Freeze-dried specimens for gross anatomy teaching - O'SULLIVAN, E. (1999)
As more and more emphasis is placed on the use of prosected specimens to support teaching and learning of gross anatomy, consideration must be given to developing new methods to preserve human cadaveric material, and in ways which will resist the wear and tear to which they are necessarily subjected. Taxidermists have developed techniques for freeze-drying whole small animals as a method of long term preservation (Metcalf, 1981). We have explored the use of this methodology to preserve small prosected specimens for use in the teaching of gross anatomy. The technique we report here was tested initially on larynges (Fig. 1) but has since been applied with equal success to other structures, including pieces of small intestine dissected to show the arterial arcades (Fig. 2). We have used material from cadavers which were preserved using our standard embalming procedure (O'Sullivan & Mitchell, 1993).